Development and Application of a Multiple Cross Displacement Amplification Combined With Nanoparticle-Based Lateral Flow Biosensor Assay to Detect Candida tropicalis - Wang, Yu; Zhao, Xue; Cheng, Jinzhi; Tang, Xiaomin; Chen, Xu; Yu, Honglan; Li, Shijun (Frontiers in Microbiology, 2021)
Candida tropicalis is an increasingly opportunistic pathogen that causes serious invasive candidiasis threatening a patient’s life.Traditional methods to detect C. tropicalis infection depends on time-consuming, culture-based gold-standard methods.So,we sought to establish a new method that could detect target pathogens quickly,accurately,and straightforwardly.Herein,a combination of multiple cross displacement amplification (MCDA) and lateral flow biosensors (LFB) was employed to detect C. tropicalis.In the MCDA system,10 primers were designed to identify the specific genes of C. tropicalis and amplify the genes in an isothermal amplification device.Then, MCDA amplification reaction products could be identified visibly by color change,and all the amplification products would be tested by LFB with no special equipment.The results demonstrated that the optimal reaction condition of C. tropicalis-MCDA assay was 64 °C within 30 min, and only 10 fg DNA was required in each reaction.No cross-reaction was found between C. tropicalis strains and non-C. tropicalis strains.For 300 sputum samples,the results showed that MCDA-LFB assay could rapidly and successfully detect all of the C. tropicalis-positive (28/300) samples detected by the gold-standard method.The entire procedure,including specimen processing (40 min), isothermal reaction (30 min) and result reporting (within 2 min),could be completed within 75 min.Briefly, the study results demonstrated that the detection ability of C. tropicalis-MCDA-LFB assay was better than culture methods with more simplicity,rapidity,sensitivity and specificity.Hence,MCDA-LFB strategy is an effective tool to rapidly detect C. tropicalis in clinical samples, especially in resource-poor areas.